CONSTRUCTION OF MATHEMATICAL MODEL OF SUSTAINABILITY OF A ROUND TIMBER PACK DURING THE OPERATIONS BY A MOBILE MACHINES - Bakay , Borys (Forestry, Forest, Paper and Woodworking Industry, 2024)
The problem of the interaction of round timber during the process of capturing levers grips mobile timber storage machines has been considered. Powered equation bend “beam system” with inclusions in elastic foundation distributed stiffness and type of loads concentrated forces. A singular functions have been used to focus inclusion in the analytical expressions of distributed parameters